2010
DOI: 10.1093/annonc/mdq028
|View full text |Cite
|
Sign up to set email alerts
|

Need for a new trial to evaluate postoperative radiotherapy in renal cell carcinoma: a meta-analysis of randomized controlled trials

Abstract: PORT significantly reduces LRF but has no effect on OS and DFS. However, due to poor patient accrual and older radiotherapy techniques in previous studies, there is a need for a new trial to evaluate PORT using conformal and intensity-modulated radiotherapy techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…However, subsequent clinical trials throughout the 1970s and 1980s failed to demonstrate any increase in survival with external beam radiation delivered in the neoadjuvant or adjuvant setting [26–29]. A meta‐analysis of seven randomized controlled trials and 735 patients treated with postoperative radiotherapy was recently published [30]. Pooled results from these trials showed a significant reduction of locoregional failure in patients treated with postoperative radiotherapy ( P < 0.001) but no difference in overall survival ( P = 0.29).…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent clinical trials throughout the 1970s and 1980s failed to demonstrate any increase in survival with external beam radiation delivered in the neoadjuvant or adjuvant setting [26–29]. A meta‐analysis of seven randomized controlled trials and 735 patients treated with postoperative radiotherapy was recently published [30]. Pooled results from these trials showed a significant reduction of locoregional failure in patients treated with postoperative radiotherapy ( P < 0.001) but no difference in overall survival ( P = 0.29).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of randomized trials of adjuvant CRT showed no significant improvement in overall or disease-free survival, although these trials were not performed in a modern RT era. 7 The main use of RT to date has been in the metastatic setting to palliate symptomatic bone and brain metastases, where short course RT doses have symptomatic benefit. 8,9 Over the past 10 to 15 years, there have been tremendous advances in RT practice, permitting use of high precision RT planning and delivery techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of RCC over last 20 years has progressively increased due to widespread use of modern imaging. 1 About 30%-50% of patients are found to have metastases at diagnosis. While bone, lymph nodes, lungs and brain constitute expected 'homing' sites, metastasis may turn up at the unusual locations (skin, testis, maxillary antrum and tongue).…”
Section: Introductionmentioning
confidence: 99%